X-ray characterisation by energy-resolved powder diffraction - Hooker, S; Cheung, G (American Physical Society, 2016)
A method for single-shot, non-destructive characterisation of broadband X-ray beams, based on energy-resolved powder diffraction, is described. Monte-Carlo simulations are used to simulate data for X-ray beams in the keV range with parameters similar to those generated by betatron oscillations in a laser-driven plasma accelerator. The retrieved X-ray spectra are found to be in excellent agreement with those of the input beams for realistic numbers of incident photons. It is demonstrated that the angular divergence of the X-rays can be deduced from the deviation of the detected photons from the Debye-Scherrer rings which would be produced by a parallel beam. It is shown that the angular divergence can be measured as a function of the photon energy, yielding the angularly-resolved spectrum of the input X-ray beam.